The alternative transcription and expression characterization of Dmc1 in autotetraploid Carassius auratus - Xu, Xidan; Wang, Chongqing; Xiao, Qingwen; Huang, Xu; Zhou, Yue; Luo, Xiang; Zhang, Yuxin; Xu, Xiaowei; Qin, Qinbo; Liu, Shaojun (Frontiers in Genetics, 2023)
Established autotetraploids often have a highly stable meiosis with high fertility compared with neo-autotetraploids. The autotetraploid Carassius auratus (4n = 200, RRRR) (4nRR), which stemmed from whole-genome duplication of Carassius auratus red var. (2n = 100, RR) (RCC), produces diploid gametes with an adopted diploid-like chromosome pairing in meiosis and maintains the formation of autotetraploid lineages. In this study, we focused on Dmc1, a meiosis-specific recombinase during the prophase of meiosis I, and elaborated on the genetic variation, alternative transcription, expression characterization, and epigenetic modification of Dmc1 in RCC and 4nRR. Two original Dmc1 from RCC were identified in 4nRR, and two duplicated Dmc1 differences in genetic composition were observed in 4nRR. Furthermore, we only noticed that one original and one duplicated Dmc1 were expressed in RCC and 4nRR, respectively. However, both possessed identical gene expression profiles, differential expression of sexual dimorphism, and hypomethylation levels. These results indicated that the specific expression of duplicated Dmc1 may be involve in the progression of meiosis of the diploid-like chromosome pairing in autotetraploid Carassius auratus. Herein, the findings significantly increase knowledge of meiosis of autopolyploid fish and provide meaningful insights into genetic breeding in polyploidy fish.